Pengembangan Jaringan Internet Sebagai Pendukung Sarana Belajar Dari Rumah Di Desa Karang Widoro Kabupaten Malang : Pengembangan Jaringan Internet Sebagai Pendukung Sarana Belajar - Agung Kridoyono; Aris Sudaryanto (Journal of Science and Social Development, 2022)
This article is a journal devotion for society that doing by educational institution especially us as a lecture to implement the threefold missions of higher education known as tridarma college. We develop a model internet network to extend internet area network as a supporting infrastructure online learning. The network that developed are the network that implemented from village hall to extend area internet area network in a densely populated student area with the wire and wireless extend network. hopefully the student have easily in online learning and more focus studying because the network had an access list website can allow operated in this network. At the end of activity, the network can help the parents of student that have a problem to provide internet for the student.